Multifaceted role of polyphenols in the treatment and management of neurodegenerative diseases. (November 2022) - Islam, Fahadul; Islam, Md Mohaimenul; Khan Meem, Atkia Farzana; Nafady, Mohamed H.; Islam, Md Rezaul; Akter, Aklima; Mitra, Saikat; Alhumaydhi, Fahad A.; Emran, Talha Bin; Khusro, Ameer; Simal-Gandara, Jesus; Eftekhari, Aziz; et al.
Abstract: Neurodegenerative diseases (NDDs) are conditions that cause neuron structure and/or function to deteriorate over time. Genetic alterations may be responsible for several NDDs. However, a multitude of physiological systems can trigger neurodegeneration. Several NDDs, such as Huntington's, Parkinson's, and Alzheimer's, are assigned to oxidative stress (OS). Low concentrations of reactive oxygen and nitrogen species are crucial for maintaining normal brain activities, as their increasing concentrations can promote neural apoptosis. OS-mediated neurodegeneration has been linked to several factors, including notable dysfunction of mitochondria, excitotoxicity, and Ca 2+ stress. However, synthetic drugs are commonly utilized to treat most NDDs, and these treatments have been known to have side effects during treatment. According to providing empirical evidence, studies have discovered many occurring natural components in plants used to treat NDDs. Polyphenols are often safer and have lesser side effects. As, epigallocatechin-3-gallate, resveratrol, curcumin, quercetin, celastrol, berberine, genistein, and luteolin have p-values less than 0.05, so they are typically considered to be statistically significant. These polyphenols could be a choice of interest as therapeutics for NDDs. This review highlighted to discusses the putative effectiveness of polyphenols against the most prevalent NDDs. Graphical abstract: Image 1 Highlights: Polyphenols may be beneficial for treating neurodegenerative diseases. Oxidative stress plays an important role in the development of neurodegeneration. Neurotrophins are considered as critical targets for polyphenols that have anti-neurodegenerative disease properties. Nanopolyphenols also shows neuroprotective properties.